2021
DOI: 10.3389/fmicb.2021.790220
|View full text |Cite
|
Sign up to set email alerts
|

Combined With Mefloquine, Resurrect Colistin Active in Colistin-Resistant Pseudomonas aeruginosa in vitro and in vivo

Abstract: Colistin is a polymyxin antibiotic that is widely used for the treatment of multidrug resistant (MDR) Pseudomonas aeruginosa infections, as the last resort. Over the past few years, unreasonable use of antibiotics has resulted in an increase in MDR strains, including colistin-resistant P. aeruginosa. The present study aimed to explore the synergistic effects of mefloquine in combination with colistin for the treatment of colistin-resistant P. aeruginosa in vivo and in vitro. The synergistic effect of the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, the combination of mefloquine-colistin might also reduce the expression of the QS system, thereby inhibiting biofilm formation. 27 In our present study, the combination of mefloquine and AS101 exhibited a significant reduction in CRPA-5 and CRPA-6 biofilms. We postulate that this effect is potentially attributed to the notable increase in bacterial cell membrane permeability and enhanced drug influx during concurrent administration.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, the combination of mefloquine-colistin might also reduce the expression of the QS system, thereby inhibiting biofilm formation. 27 In our present study, the combination of mefloquine and AS101 exhibited a significant reduction in CRPA-5 and CRPA-6 biofilms. We postulate that this effect is potentially attributed to the notable increase in bacterial cell membrane permeability and enhanced drug influx during concurrent administration.…”
supporting
confidence: 58%
“…According to reported literature, the antimalarial drug mefloquine has demonstrated the ability to significantly enhance antibacterial activity when utilized in combination with other antibacterial agents, such as colistin and antituberculosis drugs. 26,27 Based on this premise, the study employed a combination of AS101 and mefloquine for the treatment of CRPA. The chessboard assay showed that when AS101 and mefloquine were combined, the MIC of the two drugs decreased by 4-8 times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofilm inhibitory effect of NG combined with colistin was further investigated by scanning electron microscopy (SEM) ( Zhang et al, 2021b ). Reference experiments were performed with simple modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Besides our study, antimalarials, except for TAF, have demonstrated diverse antimicrobial activities. For example, artemisinin and its derivatives, mefloquine, and chloroquine have been reported to exhibit antibacterial or antifungal effects ( 19 , 42 44 ). A series of primaquine derivatives have been shown broad-spectrum antimicrobial activity ( 45 ).…”
Section: Discussionmentioning
confidence: 99%